Mental Models, Meta-Narratives, and Solution Pathways Associated With Socio-Hydrological Risk and Response in Mexico City - Eakin, Hallie; Siqueiros-García, J. Mario; Hernández-Aguilar, Bertha; Shelton, Rebecca; Bojórquez-Tapia, Luis A. (Frontiers in Sustainable Cities, 2019)
Cities are far more than the people who reside within them, the activities that drive urban dynamism, and hard and soft infrastructure that create urban structure and form. Cities are also composed of stories -- narratives -- that emerge from the experiences, ideas, knowledge and agendas of urban residents, administrators, and individuals with stakes in the city’s future. These narratives collectively not only reflect how the material landscape is perceived and socially and culturally appropriated, but also, by motivating and rationalizing human actions, contribute to shaping that material world, including the behavior and attitudes of humans within it. Here, we explore the narratives and associated solution pathways that have emerged and consolidated around the issue of water scarcity and flooding in the megalopolis of Mexico City. Effective and sustainable management of water resources has long been considered essential to the city’s future, yet many scholars consider the city “stuck” in path-dependent development trajectories that seems unable to address pervasive social inequity, infrastructure fragility, and the city’s precarious supplies. Through mental model data elicited from qualitative interviews and workshops with a cross section of urban stakeholders, we identify dominant narratives that articulate distinct causal premises and consequences associated with water related risk in the city. We juxtapose these narratives with the current and proposed solution pathways proposed by the interviewees. Our analysis demonstrates how, on the one hand, dominant narratives may quell innovation, and on the other, narratives collectively can foster the seeds of urban sustainability transformation.